O quintal que chamamos brejo: aprendizados de cuidado com o rio Peruaçu - Aline Furtado Franceschini (2023)
Waters and rivers, in addition to shaping the occupation in territories, are also a significant axis of mobilization and transmission of knowledge. They are contested territories, constantly threatened by capital interests and the ongoing environmental catastrophe. Moreover, this is where multiple ways of world-making intersect. With so many rivers and so many beings that accompany them, what are the possible ways to take care of a river? Is it possible to establish alliances between caretakers and modes of care? In this work, I move between institutional and grassroots ways of caring for the waters, and I investigate the relationships between these practices and the various forms of inhabiting the Anthropocene. I ground these questions in the Vale do Peruaçu in Minas Gerais and investigate them in correspondence with historical and everyday narratives of water care in Belo Horizonte. The work is mediated by photographic images through the construction of albums - collections that seek to build a repertoire of riverside care. I experiment with the juxtaposition of images and their narratives as a trigger for dialogues and writing. If modern technical tools are no longer sufficient to care for the damaged world, I investigate which strategies could collaborate to repair the world we share.